The Transformation of Surau Functions and the Distortion of Educational Values in Minangkabau - Metsra Wirman; Igo Fernando (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2026)
“Surau” in Minangkabau should be a place to educate the community. The objectives of this study were to determine the factors causing changes in the function of surau and how it impacts to the understanding and practice of educational values ​​in Minangkabau society. This study was conducted in Surau Gadang Syekh Burhanuddin, Ulakan, Padang Pariaman, West Sumatra. This study was a qualitative by a case study approach, data collection was carried out by observation, interviews, and documentation. The data obtained were reduced, presented, conclusion, and verification. The results of this study indicate that the factors that influence changes in the function of surau were internal and external factors. The internal factors come from the community itself, i.e., the distortion of community understanding of surau, the decline in the role of ulama and tuanku, and the decline in the quality of community faith. External factors include the influence of the modernism which causes traditional values ​​to fade and be replaced by renewal values. Surau no longer functions as a social institution in society, because there are other institutions and social institutions that are considered more relevant by the community. The impact of changes in the function of the surau on the understanding and practice of educational values ​​of the Surau Gadang Syekh Burhanuddin community includes a shift in the educational paradigm, changes in the understanding of customary and social values, and the loss of media for preserving art and culture which will threaten the sustainability of Minangkabau identity and traditions. These results are expected to provide recommendations for stakeholder to restore the surau function to its original historical.